Loop-mediated Isothermal Amplification to Detect and Identify Beer Spoilage Lactobacillus spp. Bacteria - Murakami, H.; Fujii, T.; N. Hayashi, N. Hayashi (BrewingScience, 2009)
Primers for a loop-mediated isothermal amplification (LAMP) method to specifically identify beer spoilage caused by Lactobacillus spp. including Lactobacillus brevis, Lactobacillus lindneri, Lactobacillus backi and Lactobacillus paracollinoides were developed. These LAMP primer sets were designed from target sequences in the 16S rRNA gene or the spacer region. To identify beer spoilage strains in the species, we also developed a LAMP primer set to detect highly specific genetic markers. The LAMP primer sets in this study distinguished the target species or beer spoilage strains from other lactic acid bacteria in 40–60 min. Moreover, using these primer sets in conjunction with the LAMP method enabled detection of approximately 1 x 102 cfu/ml lactic acid bacteria from suspensions in distilled water, beer and beer that contained large amounts of bottom-fermenting yeast cells. Thus, the LAMP method may be useful for direct detection and identification of Lactobacillus spp. in samples taken during the fermentation process and from final products.